Routine liver elastography could predict actuarial survival after liver transplantation - Pfeiffenberger, Jan; Hornuß, Daniel; Houben, Philipp; Wehling, Cyrill; Haken, Rebecca von; Mieth, Markus; Mehrabi, Arianeb; Weiss, Karl Heinz; Friedrich, Kilian (Journal of gastrointestinal and liver diseases, 2019)
Background & Aims: Transient elastography (TE) has routinely been implemented in the diagnosis and assessment of chronic liver disease. Little data are available in the post liver transplant (LTx) setting. - Methods: Three months after LTx, we performed TE in 137 liver transplant recipients and investigated its predictive value upon further clinical outcome. The mean follow-up time for clinical outcome was 24 months. - Results: Mean TE value was 10.6 kPa (± 6.3 kPa; range 2.8 - 29.9 kPa). There was a significant correlation between TE and aspartate aminotransferase (AST) (p=0.004), gamma-glutamyl transferase (GGT) (p=0.031) and bilirubin (p<0.001) serum levels. In Cox univariate analysis, TE served as a predictor of actuarial survival free of liver transplantation (OR=1.111, 95%CI: 1.051-1.174; p<0.001). In multivariate analysis, TE remained an independent risk factor associated with reduced actuarial survival free of liver transplantation (OR=1.080, 95%CI: 1.001-1.166; p=0.047), along with thrombocytes (OR=0.992, 95%CI: 0.986-0.999; p=0.020) and metabolic co-disease (OR = 0.250, 95%CI: 0.070-0.895; p=0.033). - Conclusion: Transient elastography measurement at three months after LTx seems a robust predictor of survival in liver transplant recipients.
Gesehen am 31.10.2019